Single- or double A-site cations in A3Bi2I9 bismuth perovskites: What is the suitable choice? - Ünlü, Feray; Kulkarni, Ashish; Lê, Khan; Bohr, Christoph; Bliesener, Andrea; Öz, Seren Dilara; Jena, Ajay Kumar; Ando, Yoichi; Miyasaka, Tsutomu; Kirchartz, Thomas; Mathur, Sanjay (Journal of materials research, 2021)
Investigations on the effect of single or double A-site cation engineering on the photovoltaic performance of bismuth perovskite-inspired materials (A 3 Bi 2 I 9 ) are rare. Herein, we report novel single- and double-cation based bismuth perovskite-inspired materials developed by (1) completely replacing CH 3 NH 3 + (methylammonium, MA + ) in MA 3 Bi 2 I 9 with various organic cations such as CH(NH 2 ) 2 + (formamidinium, FA + ), (CH 3 ) 2 NH 2 + (dimethylammonium, DMA + ), C(NH 2 ) 3 + (guanidinium, GA + ) and inorganic cations such as cesium (Cs + ), rubidium (Rb + ), potassium (K + ), sodium (Na + ) and lithium (Li + ) and (2) partially replacing MA + with Cs + in different stoichiometric ratios. Compared to single-cation based bismuth perovskite devices, the double-cation bismuth perovskite device showed an increment in the device power conversion efficiency (PCE) up to 1.5% crediting to the reduction in the bandgap. This is the first study demonstrating double-cation based bismuth perovskite showing bandgap reduction and increment in device efficiency and opens up the possibilities towards compositional engineering for improved device performance. Graphic Abstract